Feeding the mind: Nutritional strategies across different stages of Alzheimer's disease and their significance - Ahmad, Eshan; Mehmood, Asim; Inam, Rida (Journal of the Pakistan Medical Association, 2025)
Dear editor, we are writing this letter to elaborate on the significant topic of nutritional management in Alzheimer’s disease (AD), specifically at different stages of the disease progression. The nature of Alzheimer’s as a significant challenge in modern medicine necessitates a multi-faceted approach towards its management. Among these dimensions, nutritional management plays a pivotal role across all stages of the disease, from preclinical to prodromal (mild cognitive impairment) to dementia (1). Therefore, the purpose of this letter is purely to emphasise that, given the importance of nutrition in management and prevention of this malady, it is crucial that this information be discussed and disseminated more widely than it currently is. While individual nutrient supplementation has shown limited benefits, evidence suggests that a comprehensive approach to nutrition—incorporating antioxidants, polyunsaturated fatty acids, B vitamins, minerals, and polyphenols—may offer protection against oxidative and inflammatory damage in the brain (2,3). This cohesive strategy is supported by the European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines, which advocate for thorough dietary assessment, modifications, and tailored nutrient supplementation in AD patients (4). Weight loss and behavioural changes related to food are significant concerns in AD patients (5). Research indicates that interdisciplinary assistance is crucial throughout the disease course, and understanding proper nutritional guidelines is vital for effective clinical decision-making and improving patients' quality of life (5). Dysphagia, a common issue in AD, necessitates specific dietary modifications as suggested by the European Society for Swallowing Disorders (ESSD) and the European Geriatric Medicine Society (EuGMS) (4). In conclusion, recognising and addressing the nutritional needs of AD patients at each stage of the disease is essential for comprehensive care. The primary objective of this letter is to highlight the importance of nutrition and to foster a healthy discourse around the subject in the hopes of making existing strategies toward tackling Alzheimer’s Disease more efficient. This disease is one which has considerable impact on the patient’s personal and social life. Thus, out of sheer empathy, it is vital to do everything possible to assist these patients. Further research and education on this subject will equip healthcare providers with the necessary tools to make informed decisions and improve patient outcomes.